GAMBARAN RIWAYAT KELUARGA DENGAN KEJADIAN DIABETES MELLITUS TIPE 2 DI RUMAH SAKIT ISLAM SITI RAHMAH PADANG - Selvi Arianti Alfitra; Rendri Bayu Hansah; Prima Adelin; Dian ayu Hamama Pitra; Alief Dhuha (Nusantara Hasana Journal, 2023)
Background: Type 2 Diabetes Mellitus is a metabolic disorder caused by an increase in blood sugar due to decreased insulin secretion in pancreatic beta cells and/or impaired insulin function (insulin resistance). A family history of diabetes provides a useful tool to identify individuals at increased risk of developing the disease and target behavioral modifications that have the potential to prevent disease onset and improve health. Objective: To determine the family history of type 2 diabetes mellitus in patients at the Siti Rahmah Islamic Hospital, Padang. Method: The scope of this research is internal medicine. The research was conducted in August 2023 - January 2024. The type of research was descriptive quantitative with a cross sectional design. The accessible population in the study were patients suffering from type 2 diabetes mellitus who were taken based on the results of patient interviews at RSI Siti Rahmah Padang with a total of 50 samples using a purposive sampling technique. Univariate data analysis is presented in the form of a frequency distribution and data processing using the computerized SPSS program IBM version 25.0. Results: The frequency distribution of family history of type 2 diabetes mellitus from father was 11 people (22.0%), mother was 14 people (28.0%), both parents were 9 people (18.0%), siblings biological, namely 3 people (6.0%), parents and siblings, namely 4 people (8.0%) and no family history, namely 9 people (18.0%). Conclusion: The mother has the most family history in type 2 diabetes mellitus patients at the Siti Rahmah Islamic Hospital, Padang.